An Analysis of South Africa's Constitutional and UNCRC-imposed Obligations to Achieve Children's Socio-economic Rights: A Critique - Tshilidzi Knowles Khangala (Athens Journal of Humanities & Arts)
Children require specific protection due to their heightened vulnerability to human rights violations, which can be attributed to several factors such as economic adversity, racial tensions, and armed conflicts. The current situation in South Africa is characterised by a pressing and significant prevalence of severe poverty. The enduring effects of apartheid have contributed to a broad range of socioeconomic challenges inside our deeply divided country. Children are particularly impacted by these issues and experience immediate suffering as a result. In the Republic of South Africa, a significant proportion of the youth population experiences the distressing circumstance of living in poverty. It has been reported that a significant proportion, ranging from 60 to 75 percent, of the youth population in South Africa is experiencing impoverished living conditions. The prevalence of HIV infection and the consequential mortality rates due to AIDS among caretakers have a detrimental effect on the well-being of children. The United Nations Convention on the Rights of the Child (UNCRC) encompasses social, economic, and cultural rights under its provisions. Following the ratification of the UNCRC in June 1995, South Africa is legally obligated to implement the articles pertaining to the rights of children. The formulation and structuring of socio-economic rights and corresponding duties towards children under the South African Constitution were significantly influenced by the UNCRC. The interests of children in South Africa are effectively safeguarded through the provisions enshrined in the Constitution and the duties outlined in the UNCRC. This study assesses the extent to which South Africa has adhered to its constitutional and UNCRC-mandated responsibilities and commitments in order to achieve the socioeconomic rights of children